Agrobiodiversidad: Validación E Identificacion De Flora En La Comunidad Piñancay, Parroquia Capsol, Chunchi-Ecuador - Pacheco, Edmundo Danilo Guilcapi; Cruz, Carlos Alberto Rivera; Cruz, Lisseth Paola Ortiz (European Scientific Journal, ESJ, 2017)
Ecuador is considered as a country with great biodiversity, in spite of its small territory. This is due to multiple factors including geographic location, geological, topographical and climatic factors, precipitation, temperature, and location in the tropical belt of the planet. On the equinoctial line, with territories located both in the northern hemisphere and in the southern hemisphere, all this forces us to maintain a constant responsibility towards our flora and fauna for its conservation and wealth. Piñancay is one of the six (6) communities of the Capsol parish, which belongs to the Chunchi canton. It has a cold, humid, and cloudy climate that allows the development of agricultural activities on a wide range. It however serves as a form of income to the inhabitants of the sector. Thus, based on the validation and identification of the flora inventory of the Piñancay community and in addition to the morphological and taxonomic identification of the plants, a study was carried out on the current agrobiodiversity of the Piñancay community.